Automatic floor tiling robot / Khaznida Kamarudin and Nurul Huda Abdul Hadi - Kamarudin, Khaznida; Abdul Hadi, Nurul Huda (2023)
Tiling is a finishing work, considered one of the important elements in building construction. The main purpose of tile installation is to enhance the overall appearance of the building. It is important to ensure that the installation work is executed with high quality, ensuring completion without any issues or problems. The conventional method of tile installation in the construction industry often encoounters various problems and issues, both during and after the construction process. This includes challenges such as filth, dust, noise, dirt, and vibrations that can pose risks to the workers. Therefore, transitioning away from conventional methods and embracing construction automation, such as robots in the construction industry, are promising ideas for future competitiveness. The process involved identifying current problems, proposing and developing a new machine, and assessing the marketability of the product.